Fluoroscopic lumbar transforaminal epidural steroid injections for recurrent herniated intervertebral disc after discectomy: Effectiveness and outcome predictors - Um, Mi-Kyung; Lee, Eugene; Lee, Joon Woo; Kang, Yusuhn; Ahn, Joong Mo; Kang, Heung Sik (PloS one, 2022)
Despite transforaminal epidural steroid injection (ESI) being the first choice in patient with recurrent herniated intervertebral disc (HIVD), efficacy of ESI in those patients are not well established. Herein, we evaluate the effectiveness and outcome predictors of fluoroscopic transforaminal ESI for recurrent HIVD. Seventy-seven patients (48 male; mean age, 51.3 years) with recurrent lumbar HIVD were included and divided into three groups according to initial treatment: conservative treatment, transforaminal ESI, and immediate surgery. ESI effectiveness was evaluated by operation rates, injection numbers in 6 months, and pain reduction (visual analog scale (VAS) scores). Clinical and MRI variables were analyzed as possible outcome predictors. Each subject in the transforaminal ESI group was individually matched to two patients with initial HIVD (control group). In the transforaminal ESI group (n = 37), 20 patients (54.1%) did not undergo reoperation. The initial and follow-up VAS scores were significantly higher in the reoperation group (p = 0.014, p = 0.019, respectively). Patients with either paresthesia or motor weakness (12/19, 63.2%) had a significantly higher reoperation rate than patients with only pain (5/18, 27.8%; p = 0.031). Extruded disc ratios [greater than or equal to]2.0 were significantly higher in the reoperation group (10/17, 58.8%; p = 0.048). The reoperation rate in the transforaminal ESI group (17/37, 45.9%) was higher than the operation rate in the control group (6/73, 8.2%; p<0.001). Transforaminal ESI was effective in reducing radicular pain in patients with recurrent HIVD. Approximately 54% of patients did not undergo reoperation. An extruded disc ratio [greater than or equal to]2.0 and paresthesia or motor weakness were poor outcome predictors.